Diseño de un soporte en transporte público para amputados de miembro superior (2012)
This project includes the design of a public transport support for upper limb amputees, as the current prosthetic systems do not provide patients with the security and necessary comfort, and cause, therefore, great difficulties when traveling. The designed support system offers the largest current prosthetic functions, mainly a more comfortable and safe mobility in the public transport system. This translates into better quality of life for people who have suffered some type of upper limb amputation.